Self-care Maintenance of Heart Failure Patients in Babylon Teaching Hospitals - Ameer Hassan (Journal of Global Pharma Technology, 2018)
Heart failure (HF) is currently one of the major public health problems in world, and its complex and gradual nature often results in reverse proceedings, such as high rate of rehospitalization and mortality, which could be reduced if there were appropriate self-care, therefore, Self-care is one of the most significant aspects of the treatment of patients with heart failure through using special activities to reduce and relieve symptoms and maintain and promote health in patients. Quantitative research, descriptive design cross sectional study Non-probability purposive sample consisted of (100) heart failure patients who admitted to the Babylon teaching hospitals were selected .The finding out of the study show most of the patient with heart failure have moderate self-care management a high significant difference between the self-care ability and their body mass index levels. a significant difference between this disease and their chronic diseases, hypertension, diabetes mellitus and duration of disease.Keywords: Self-care, Management, Heart failure patients, Babylon teaching Hospitals.